2020
DOI: 10.1007/s00134-020-06219-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal superinfections in critically ill patients with COVID-19

Abstract: Are critically ill patients with coronavirus disease 2019 (COVID-19) at high risk of bacterial and fungal superinfections developing on the top of the viral infection in the lung or in other body sites? And from which organisms? Answering these apparently simple questions could be far more difficult than expected, for at least three important reasons. The first one is that the timing of development of superinfection (early or late) with respect to the intensive care unit (ICU) admission may have relevant clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
90
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 18 publications
5
90
1
2
Order By: Relevance
“…Although debate continues regarding the differences and similarities between influenza and COVID-associated aspergillosis [10], in keeping with our findings in bacterial VAP it appears that IPA is more common in COVID-19 patients than in ICU patients without COVID-19. It has been suggested that CAPA may relate to the use of immunosuppressive medications [10]. As can be seen from Table 1, steroids were relatively rarely used in this cohort of COVID-19 patients who were largely admitted before the results of the RECOVERY trial had been announced [24] and indeed none of the 3 CAPA patients we identified had received steroids prior to their diagnosis or had underlying immunosuppressive conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although debate continues regarding the differences and similarities between influenza and COVID-associated aspergillosis [10], in keeping with our findings in bacterial VAP it appears that IPA is more common in COVID-19 patients than in ICU patients without COVID-19. It has been suggested that CAPA may relate to the use of immunosuppressive medications [10]. As can be seen from Table 1, steroids were relatively rarely used in this cohort of COVID-19 patients who were largely admitted before the results of the RECOVERY trial had been announced [24] and indeed none of the 3 CAPA patients we identified had received steroids prior to their diagnosis or had underlying immunosuppressive conditions.…”
Section: Discussionsupporting
confidence: 87%
“…There is increasing recognition of fungal infections amongst patients with viral pneumonitides and VAP [ 11 , 21 , 22 ]. Although debate continues regarding the differences and similarities between influenza and COVID-associated aspergillosis [ 10 ], in keeping with our findings in bacterial VAP it appears that IPA is more common in COVID-19 patients than in ICU patients without COVID-19. It has been suggested that CAPA may relate to the use of immunosuppressive medications [ 10 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Even though the AspICU algorithm to diagnose invasive pulmonary aspergillosis in critically ill patients requires a positive respiratory culture to identify Aspergillus , the real prevalence remains elusive because of the current absence of a standardized definition for non-proven disease in non-neutropenic critically ill patients. 8 , 9 Nine multidrug-resistant strains were isolated, which represented 6% of microbial isolates: extended-spectrum beta-lactamase E. coli (4); multi-resistant P. aeruginosa (2), and methicillin-resistant S. aureus (3).…”
mentioning
confidence: 99%
“…Furthermore, multiple criteria for IPA diagnostic are available, and the most reliable for COVID-19 patient are presently being determined, as was recently the case for IAPA [7] . Whereas, as recently noted by experts [13] , there exists no perfect definition, we strongly believe the most realistic one should focus on specificity, as Asp-ICU, focuses on specificity. Depending on the criteria used, the number of cases might support major variations, thereby underlining the importance of carefully choosing which definition to use.…”
Section: Discussionmentioning
confidence: 86%